A transparent, ultrastretchable and fully recyclable gelatin organohydrogel based electronic sensor with broad operating temperature. Issue 8 (12th February 2020) - Qin, Zhihui; Sun, Xia; Zhang, Haitao; Yu, Qingyu; Wang, Xueyuan; He, Shaoshuai; Yao, Fanglian; Li, Junjie
Abstract : A green, fully recyclable and stretchable electronic sensor based on ionic conductive gelatin organohydrogels can operate at ultra-low temperature. Abstract : Flexible and stretchable electronics have received tremendous attention for next-generation human-friendly electronic applications. However, fabrication of transparent, fully recyclable and stretchable electronic sensors with low-temperature stability using biocompatible natural polymer-based hydrogels still remains a great challenge. In this study, a green and fully recyclable stretchable electronic sensor with high transparency and ultra-low operating temperature is constructed using ionic conductive gelatin organohydrogels. These gelatin organohydrogels are prepared by a simple strategy of immersing gelatin pre-hydrogels in citrate (Na3 Cit) water/glycerol solutions. The existence of Na3 Cit in the organohydrogel not only induces the formation of multiple non-covalent cross-linking points, endowing the organohydrogel with high mechanical performances, but also makes the organohydrogel have excellent ionic conductivity. The organohydrogel is also highly transparent and exhibits outstanding antifreezing properties. The mechanical robustness, conductivity and transparency of the organohydrogel can be well maintained even at −60 °C. As a result, a stretchable and transparent electronic sensor based on this organohydrogel is fabricated, which is strain-sensitive with a large linear sensing window and excellent stability. More importantly, the organohydrogel-based electronic sensor can be fully recycled due to the reversible non-covalently crosslinked structure, and the recycled organohydrogel regains its mechanical and sensing properties. The obtained sensors could precisely detect various human activities even below −30 °C, indicating the potential applications of the organohydrogel-based electronic sensor in flexible and stretchable electronics in a broad range of temperature.